Initiation of Cell Suspension Cultures from Axenic Leaf Explants of Lentisk (Pistacia lentiscus L.) - Hoser, Ayse; Demir, Elif; Asan, Hilal Surmus; Suzerer, Veysel; Tilkat, Engin; Ertas, Abdulselam; Onay, Ahmet (Springer, 2017)
[No abstract available]